2012
DOI: 10.1371/journal.pone.0048083
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Stress on Female Mice Diminishes the Developmental Potential of Oocytes: A Study Using the Predatory Stress Model

Abstract: Although the predatory stress experimental protocol is considered more psychological than the restraint protocol, it has rarely been used to study the effect of psychological stress on reproduction. Few studies exist on the direct effect of psychological stress to a female on developmental competence of her oocytes, and the direct effect of predatory maternal stress on oocytes has not been reported. In this study, a predatory stress system was first established for mice with cats as predators. Beginning 24 h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 52 publications
4
26
0
Order By: Relevance
“…Similar results were obtained in response to dexamethasone in cultured rat preovulatory follicles [116]. Although glucocorticoids seem to impair oocyte development in vitro by increasing apoptosis [117], no alterations in oocyte maturation have been reported in response to high circulating levels of glucocorticoids in vivo [118]. However, the same study highlighted a decreased blastocyst formation, suggesting that glucocorticoids may alter the oocyte potential for fertilization rather than oocyte maturation.…”
Section: Glucocorticoids and Reproductive Functionsupporting
confidence: 72%
“…Similar results were obtained in response to dexamethasone in cultured rat preovulatory follicles [116]. Although glucocorticoids seem to impair oocyte development in vitro by increasing apoptosis [117], no alterations in oocyte maturation have been reported in response to high circulating levels of glucocorticoids in vivo [118]. However, the same study highlighted a decreased blastocyst formation, suggesting that glucocorticoids may alter the oocyte potential for fertilization rather than oocyte maturation.…”
Section: Glucocorticoids and Reproductive Functionsupporting
confidence: 72%
“…showed early life stress was associated with disconfiguration of oocyte chromatin, which reduced the developmental competence . To investigate the psychological stress on the development of mouse oocytes, Liu et al ., put a cat next to a mouse cage as a hunter model and found that psychological stress can reduce the developmental competence of the oocytes and result in the decrease of the rate of blastocyte formation. Bhat et al ., also examined the effect of maternal separation stress on atresia in ovarian follicles and showed that stress causes apoptosis in granulosa cells of follicles .…”
Section: Discussionmentioning
confidence: 99%
“…An increase in plasma cortisol levels along witb increasing corticosteroid-binding globulin (CBG) levels stimulate maternal metabolism and tbe mobilization of maternal resources to sustain embryo requirements (Nolten & Rueckert, 1981;Laudat et al, 1987). However, tbe elevation of plasma glucocorticoid levels is considered a double-edged process because wben abundantly released under stressful conditions tbese bormones can perturb reproduction (Breuner et al, 2008;Liu et al, 2012). Indeed, abundant release of glucocorticoids caused by a stimulation of tbe bypotbalamic-pituitary adrenal axis (HPA) can perturb tbe bypotbalamic-pituitary gonadic axis; for instance via tbe inbibition of tbe secretion of luteinizing bormone, and consequently can negatively impact tbe ovarian secretion of essential sex steroid bormones (Cbatterton, 1990;Magiakou et al, 1997).…”
Section: Introductionmentioning
confidence: 99%